Predicition Molecular Docking, Pharmacokinetic, Physicochemical, Toxicity, Synthetic Accessibility Aspect of Several Compounds in Cratoxylum glaucum and Cratoxylum arborescens as Antimalarial - Suryanto, Suryanto; Muslikh, Faisal Akhmal; Nahdhia, Nadhifatun; Susilawati, Delis (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to identify potential antimalarial compounds targeting the Plasmodium falciparum lactate dehydrogenase enzyme (PfLDH), given the parasite's dependency on glycolysis for energy production. Considering the high similarity of LDH enzymes across Plasmodium species, developing novel PfLDH inhibitors may offer therapeutic benefits, particularly against P. vivax, P. malariae, and P. ovale. Computational approaches were employed to screen natural compounds from the Cratoxylum genus (Cratoxylum glaucum and Cratoxylum arborescens). Molecular docking was performed using Molegro Virtual Docking (MVD) to assess binding affinity. SwissADME was utilized to evaluate pharmacokinetic, physicochemical, synthetic accessibility properties, and ProTox II was used for toxicity prediction. Molecular docking results indicated that fuscaxanthone C and 3-geranyloxy-6-methyl-1,8-dihydroxyanthraquinone exhibited strong inhibitory activity against PfLDH, with rerank scores of -103.068 kcal/mol and -111.141 kcal/mol, respectively surpassing the reference ligand chloroquine (-94.307 kcal/mol). Pharmacokinetic analysis revealed that all compounds, except stigmasterol and fuscaxanthone C, met Lipinski’s Rule of Five. Toxicity prediction categorized fuscaxanthone C as Class III (toxic). Additionally, synthetic accessibility predictions indicated that all compounds, except stigmasterol, are easy to synthesize. Natural compounds from the Cratoxylum genus, particularly 3-geranyloxy-6-methyl-1,8-dihydroxyanthraquinone, show promise as PfLDH inhibitors. Despite its potency, fuscaxanthone C's toxicity profile warrants caution. Further studies are needed to validate these findings through in vitro and in vivo testing.